2019
DOI: 10.1002/amp2.10021
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural porosity in additive manufacturing: The formation and detection of pores in metal parts fabricated by powder bed fusion

Abstract: Metal additive manufacturing (AM) is an innovative manufacturing technique that can build complex and high value metal parts layer by layer using a computerized three‐dimensional solid model. Powder bed fusion (PBF) is one of the most common AM techniques. It sequentially processes a powdered feedstock in thin layers and solidifies it by either a laser beam or an electron beam. However, PBF induces microstructural defects that can adversely affect the performance of the manufactured components. These undesirab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
87
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 244 publications
(89 citation statements)
references
References 72 publications
1
87
0
1
Order By: Relevance
“…A lack of fusion appears between layers as partially or fully unmelted particles [16] if the scan speed and laser power do not provide the energy density required for normal melting [17]. Moreover, the volumetric heat capacity gradient induced by differences in the size of powder particles results in fusion defects as well [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A lack of fusion appears between layers as partially or fully unmelted particles [16] if the scan speed and laser power do not provide the energy density required for normal melting [17]. Moreover, the volumetric heat capacity gradient induced by differences in the size of powder particles results in fusion defects as well [18].…”
Section: Introductionmentioning
confidence: 99%
“…Voids normally arise due to the entrapment of gas bubbles during the laser melting process [17]. However, at a low laser density, voids can be formed due to the entrapment of powder particles if the melt pool is small; therefore, the particles are not molten enough to ensure sufficient bonding [19].…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that this type of dimensional defects along with surface roughness can be caused by powders denudation as a result of high-pressure gas flow which affects the height of the melt track and extend the denudation phenomenon [21,22]. Moreover, rapid melting and solidification of metallic material generate high residual stresses that lead to defects such as microfractures and delamination between layers and formation of elevated edges or corners along with formation of key-hole porosities near the part's edge where heat can accumulate [23].…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that defects including voids and porosities are prone to form near the edges than in the core. This is associated to the different core and contour scanning strategies where the speed and direction of the laser beam are changed [23]. Accordingly, when it is seeking to obtain high relative density parts then no contour scanning strategy is often preferred.…”
Section: Introductionmentioning
confidence: 99%
“…[2] Another important theme for the journal has been the design and study of modular and intensified processes, [10][11][12][13] and the technologies that can support them, such as 3D printing and other additive manufacturing techniques. [14] Neal et al [11] propose a modular ethane-to-liquids system based on using chemical looping oxidative dehydrogenation technology to convert ethane and natural gas liquids via cyclic redox reactions of highly effective redox catalyst particles. This technology eliminates air separation and equilibrium limitations for olefin generation.…”
mentioning
confidence: 99%